HADITS DITINJUAN DARI KUALITASNYA - Delisa Delisa; Ahmad Zabidi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Hadith is every word, action, or decree attributed to the Prophet Muhammad SAW. In other languages, hadith is any information attributed to the Prophet Muhammad SAW. For example, when we say "Rasulullah SAW once said" or "Rasulullah SAW once did...", indirectly this statement can be said to be a hadith. But the question is, is this statement really what the Prophet said or not? Because it is not certain that every information in the name of Rasulullah is truly valid and there is also a lot of news about Rasulullah that is faked for certain purposes. Therefore, knowing the truth of information in the name of the Prophet (hadith) is very important. Hadith scholars divide hadiths based on their quality into three categories, namely authentic hadiths, hasan hadiths, and dhaif hadiths.